Hook, Lyin' & Sinker : A Tangle of Fishing Humor - Peterson, Brian R. (Essex, Connecticut : Lyons Press, 2023)
"A collection of the best and funniest jokes and cartoons about fishing, with special emphasis on bass fishing (and gear) and fly fishing. Companion outdoor book to Laughing it Up in Deer Camp, Hook, Lyin' & Sinker is an unusually rich collection of fishing humor not found elsewhere. A good humor book for those of good humor, smartly curated for all ages and genders. It's for people who may or not fish who need a laugh or want to give a laugh to friends and family members who fish any water, any fish species, and any technique"--
Bibliography: pages 124-126.
Keywords: Gardens -- Connecticut; Gardens -- Connecticut -- Pictorial works